THE ANALYSIS OF DIVERSIFICATION TENDENCIES IN THE REGIONAL INNOVATIVENESS OF EU COUNTRIES 1999-2012 - Markowska, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The measurement of innovation, the role of which in economic processes is mainly analysed in the context of competitive position, is applied in the assessment of both enterprises and economy sectors, as well as with reference to particular countries, regions and municipalities. Innovative activities, as M. E. Porter emphasises, allow for particular territories to achieve a competitive advantage.The objective of this paper is to present the results of seeking an answer to the question about the changes which have occurred in regional innovation diversification in the European Union countries in the period 1999-2012.The realisation of this defined goal requires determining the value of the innovation indicator for each EU NUTS-2 level region based on the characteristics describing regional innovation in dynamic perspective. The study presents an algorithm for this indicator specification, as well as the statistical properties it covers.This is followed by calculating the standard deviation for the EU regions in each year of the study (excluding countries with just one NUTS-2 level region). The estimated linear and exponential trends, including the slope coefficients significance testing, are to indicate the countries characterised by stable diversification as well as those where regional differences became more extensive.